2016
DOI: 10.5604/12321966.1203898
|View full text |Cite
|
Sign up to set email alerts
|

The influence of caffeine administered at 10°C on bone tissue development

Abstract: Introduction and objective. Caffeine is a natural methylxanthine widespread throughout the food industry. Many research studies have shown that caffeine readily crosses the placenta causing teratogenic and embryotoxic effects. The objective of this study was to assess the influence of caffeine, administered at 10°C, on the development of a rat's bone tissue, with particular reference to elemental bone composition using an X-ray microprobe. Materials and methods. The research was conducted on white rats of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…study, they gave 30 mg/kg caffeine orally to pregnant rats and examined the bone / cartilage ratio of fatuses by the double skeletal staining method. As a result of their studies, they reported that the bone ratio of fetuses exposed to caffeine was lower than the control group [20]. Yılmaz et al (2018), investigated the protective effects of melatonin against the effects of nicotine on bones in their study; and found that the percentage and rate of ossification was low in the upper and lower extremity bones of the group to which 6 mg/kg nicotine was administered (31.42 ± 10.33) compared to the control group (43.71 ± 2.33).…”
Section: Dıscussıonmentioning
confidence: 97%
“…study, they gave 30 mg/kg caffeine orally to pregnant rats and examined the bone / cartilage ratio of fatuses by the double skeletal staining method. As a result of their studies, they reported that the bone ratio of fetuses exposed to caffeine was lower than the control group [20]. Yılmaz et al (2018), investigated the protective effects of melatonin against the effects of nicotine on bones in their study; and found that the percentage and rate of ossification was low in the upper and lower extremity bones of the group to which 6 mg/kg nicotine was administered (31.42 ± 10.33) compared to the control group (43.71 ± 2.33).…”
Section: Dıscussıonmentioning
confidence: 97%
“…Then, the obtained photos were transferred to computer. The Image J Program was employed for length-area measurements of bones (10,18,24).…”
Section: Skeletal Staining In Fetusesmentioning
confidence: 99%
“…Also, it was speculated that high caffeine doses may accepted as risk-increasing for osteoporosis in adults (9). In addition, to cause mineralization abnormalities in carpal and metatarsal bones, skull, pelvic belt, sternum, and spine bone tissue were reported (10,11). Researchers are extensively focusing on the mechanism-based effects of antioxidants in different diseases (12,13).…”
Section: Introductionmentioning
confidence: 99%